FORMULASI SEDIAAN LIPSTIK EKSTRAK DAUN JATI (Tectona grandis L., f.) SEBAGAI ZAT PEWARNA - Sutaryono; Anita agustina; Indah Sukmawati (STIKES MUHAMMADIYAH KLATEN, 2018)
Teak leaves (Tectona grandis L., f) include familia verbenaceae that have strong antioxidant activity. The color of the teak leaves is caused by the flavonoid that is antosianidin. Anthocyanidin is a pigment that can be used as a natural dye and can replace synthetic dyes. The purpose of this study was to formulate lipstick preparations using dyes contained in teak leaves and to determine the effect of variation of teak leaf extract concentration. The type of research used is experimental research. This research covers teak leaf extraction using maseration method. Lipstick is made in 3 formulas. Formula I with concentration 5%, formula II 7% concentration and formula III 9% concentration. Lipstick that has been made then tested by physical properties including organoleptc test, homogeneity test, pH test, melting point test, and hardness test. The resulting lipstick is stable, red brick, brownish and light brown. The melting point of lipstick preparation containing teak leaf extracts with concentration of 5%, 7% and 9% were 55,670C; 57,330C and 58,670C, respectively, while the pH of lipstick preparations were respectively 6; 5 and 4. Hardness of lipstick preparations with concentrations of 5%, 7% and 9% were 87 grams, 97 grams and 112 grams, respectively. The conclusion of the research showed that the lipstick formulation of teak leaf extract can be used as a dye and there is influence of variation of teak leaf extract concentration.